Manajemen Beberapa Fibroid Rahim Pada Kehamilan - Kadek Agus wijaya; Ni Made Youthma Dwistayani (Jurnal Health Sains, 2022)
ABSTRACT Uterine Fibroids is a benign tumors originating from the smooth muscle of the uterus. In general, uterine myomas are asymptomatic and are found incidentally during ultrasound examination of pregnancy. We report that a 39-year-old woman with G2P1001 who admitted she was 40 weeks pregnant came with complaints of intermittent abdominal pain since 04.00 in the morning, which was getting worse 2 hours before being admitted to the hospital. Complaints are accompanied by the discharge of blood mucus through the vagina. The patient was married 2 times and the distance between the first child and the second was 19 years. The patient's vital signs were within normal limits. On physical examination, there was a palpable mass with a smooth surface that seemed to stick to the uterus. Obstetrical examination revealed: uterine fundal height: 32cm, HIS + adequate, fetal heart rate 140 beats/minute, performance; head position. When a vaginal touch was performed, it was found that there was an opening of 1 cm with 25% thinning, and the membranes were still intact. The patient was diagnosed with G2P10001  40-41 weeks of gestation + single alive Intra uterine + old secondary primary + uterine fibroids. The patient underwent a cesarean section, and the outcome of the baby and mother was good. Intraoperative findings found that 2 uterine myomas were measuring more than 5 cm located in the subserosa and intramural so the patient underwent a supravaginal hysterectomy. The age of the patient above 35 years is one of the considerations for tubectomy.